2010
DOI: 10.1016/j.ejcts.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ischaemic mitral regurgitation. Current treatment results and new mechanism-based surgical approaches☆

Abstract: Chronic ischaemic mitral regurgitation (CIMR) remains one of the most complex and unresolved aspects in the management of ischaemic heart disease. This review provides an overview of the present knowledge about the different aspects of CIMR with an emphasis on mechanisms, current surgical treatment results and new mechanism-based surgical approaches. CIMR occurs in approximately 20-25% of patients followed up after myocardial infarction (MI) and in 50% of those with post-infarct congestive heart failure (CHF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 173 publications
(247 reference statements)
2
82
0
6
Order By: Relevance
“…Moreover, The American Nurses Association reported that nurses' stress occurs as a result of Physical violence by patients, patients' family members, or strangers against nurses or by "lateral", violence in the form of incivility, disruptive behavior, verbal aggression, and bullying tend to be perpetrated by other nurses, nurse managers, physicians, and other co-workers. [11] In disagreement with the previous study findings, Haybatollahi [19] conducted a study about stress on military nurses and indicated that nurses reported high level of job stress as a result of lack of support from supervisors, high responsibility, long working hours, and role overload. Moreover, Swedish' study of stress among a large sample of nurses revealed that most study nurses reported high to very high level job stress.…”
Section: Published By Sciedu Pressmentioning
confidence: 71%
“…Moreover, The American Nurses Association reported that nurses' stress occurs as a result of Physical violence by patients, patients' family members, or strangers against nurses or by "lateral", violence in the form of incivility, disruptive behavior, verbal aggression, and bullying tend to be perpetrated by other nurses, nurse managers, physicians, and other co-workers. [11] In disagreement with the previous study findings, Haybatollahi [19] conducted a study about stress on military nurses and indicated that nurses reported high level of job stress as a result of lack of support from supervisors, high responsibility, long working hours, and role overload. Moreover, Swedish' study of stress among a large sample of nurses revealed that most study nurses reported high to very high level job stress.…”
Section: Published By Sciedu Pressmentioning
confidence: 71%
“…The leaflets appear tethered but are otherwise normal (Figure 1). 3,4 Clinically, this will be apparent with evidence of prior myocardial infarction by typical ECG findings and/or wall motion abnormalities on echocardiography. Appropriately correlative findings on cardiac catheterization or other appropriate imaging technique confirm the ischemic etiology.…”
Section: Definitionmentioning
confidence: 99%
“…No survival benefit has been demonstrated at 10 years compared with CABG alone. 4 Indications for surgery in this group are inadequately defined and based on general consensus. Surgery performed for IMR ranges from CABG alone to CABG and mitral valve surgery.…”
mentioning
confidence: 99%
“…Expansion of the posterior wall pushes the posterior papillary muscle outward and inferiorly, tethering the mitral leaflet and causing mitral insufficiency [4][5][6][7]. Left ventricular wrapping with Merseline mesh before the creation of an MI was reported to prevent posterior wall expansion and ischemic mitral regurgitation [8].…”
Section: Introductionmentioning
confidence: 98%